Perancangan Prototype UI/UX Website Softcoffee Dengan Penerapan Metode Design Thinking - Sitorus, Herdiyanti Ratiningsih; Ibrahim, Ali; Yadi Utama; Hardini Novianti (STMIK Budi Darma, 2024)
The advancement of information technology plays a crucial role in supporting businesses, including the coffee industry exemplified by Softcoffee Lintang. Softcoffee Lintang faces challenges with its manual ordering system and limited promotions, which hinder customers from easily accessing essential information such as prices, menus, and current promotions. This study employs the Design Thinking methodology to develop an innovative web-based User Interface (UI) and User Experience (UX) aimed at addressing these issues and enhancing the customer experience. A qualitative approach, involving interviews with management and questionnaires to customers, revealed that the resulting UI/UX design significantly facilitates application use, incorporating new features such as additional payment methods and product reviews, which received Single Ease Question (SEQ) scores above 6. The Design Thinking methodology proved effective in enhancing Softcoffee Lintang's operational efficiency through an attractive and intuitive website design, providing practical solutions to the identified problems and supporting the overall business strategy